TEAM GAMES TOURNAMENT AND MEANS-ENDS ANALYSIS: LEARNING TYPES IN IMPROVING MATHEMATICAL CRITICAL THINKING - Samtari, Nurin; Fakhriyana, Dian (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
The purpose of this research was to determine the effectiveness of Teams Games Tournament (TGT) and Means-Ends Analysis (MEA) learning types in improving mathematical critical thinking skills and to compare the effectiveness of the two learning types. This research used a quantitative approach with a purposive sampling technique. Two classes were selected from all XI classes at MA Ma'ahid Kudus: experimental class 1, which applied the TGT learning type, and experimental class 2, which applied the MEA learning type. Both experimental classes were chosen based on the pretest homogeneity test, and the two classes were homogeneous. The results obtained from this research are as follows: 1) There is an increase in students' mathematical critical thinking skills after being given the TGT learning type, 2) There is an increase in students' mathematical critical thinking skills after being given the MEA learning type, and 3) There is a difference in effectiveness between the TGT and MEA cooperative learning models.